Dark fermentative hydrogen production from pretreated lignocellulosic biomass: Effects of inhibitory byproducts and recent trends in mitigation strategies. (November 2020) - Basak, Bikram; Jeon, Byong-Hun; Kim, Tae Hyun; Lee, Jae-Cheol; Chatterjee, Pradip Kumar; Lim, Hankwon
Abstract: Lignocellulosic biomass (LCB) is expected to play a significant role in achieving the goal of biomass-to-bioenergy conversion due to its wide distribution and low price. Acidogenic dark fermentation of LCB is a promising approach to the sustainable production of biohydrogen (bioH2 ) from this valuable substrate. Because of its inherent recalcitrance, LCB requires pretreatment to increase its digestibility and enable its improved utilization. Intense thermochemical pretreatments solubilize the lignin and hemicellulose and lead to the formation of a variety of inhibitory byproducts, such as short-chain carboxylic acids, furfural, 5-hydroxymethylfurfural (5-HMF), vanillin, and syringaldehyde, which interfere with the physiological and metabolic functions of dark fermentative microbiota, thus inhibiting bioH2 production. To offset the negative impacts of these inhibitors on bioH2 production, approaches to detoxify lignocellulosic hydrolysates have been considered. This review comprehensively discusses the generation of lignocellulosic inhibitory byproducts in commonly used, contemporary pretreatment regimens and their inhibitory effects on dark fermentative H2 production. Furthermore, the mechanisms of inhibiting H2 producing bacteria and their effects on bacterial community dynamics in mixed cultures are reviewed. State-of-the-art strategies for detoxifying pretreated LCB are discussed. The selection of desirable alternative lignocellulose pretreatment strategies that produce less or no inhibitory byproducts are highlighted. Finally, this review discusses the economic aspects of bioH2 production from LCB, considering the pretreatment and detoxification process. Given the limitations of previous studies, future research for developing cost-effective strategies to overcome byproduct inhibition during dark fermentation of pretreated LCB are suggested. Highlights: The effects of lignocellulosic inhibitors on bioH2 production are discussed. The mechanisms of action of inhibitors on bioH2 -producing bacteria are elucidated. The changes in H2 -producing microbiota structure due to inhibitors are interpreted. State-of-the-art strategies to mitigate problems caused by inhibition are reviewed. In situ detoxification allows the removal of inhibitors during dark fermentation.